Cover Image. (28th May 2019) - Rudra, Soumon; Jiang, Naomi; Rosenberg, Stephen A.; Olsen, Jeffrey R.; Roach, Michael C.; Wan, Leping; Portelance, Lorraine; Mellon, Eric A.; Bruynzeel, Anna; Lagerwaard, Frank; Bassetti, Michael F.; Parikh, Parag J.; et al.
Abstract : The cover image is based on the Original Research Using adaptive magnetic resonance image‐guided radiation therapy for treatment of inoperable pancreatic cancer by Soumon Rudra et al., DOI: 10.1002/cam4.2100 .